Analysis of Resonance Characteristic of the Transmission System of an Aeroengine Accessory - Gao Xuepeng (Jixie chuandong)
A simplified analysis model of aeroengines transmission system is established by using the concentrated mass method,and the dynamics equations of the transmission system are deduced according to this model. The nature modal of the system is analyzed by using the shaft element method. The nature modal of rotor system and the coupled modal of the system are calculated. Through the comparison of the two kinds of modal,it is found that the coupling transmission system contains not only the single axial modal and bending- torsiona- coupled modal dominated by a single axis,but also derived new bending- torsiona- coupled modal which is very sensitive to the gear coupling. The natural frequency of the rotor under different operating speeds is analyzed by using the Campbell diagram,which provides the basis for the analysis of the resonance characteristic of the system.